A Cobalt‐Catalyzed Alkene Hydroboration with Pinacolborane1. Issue 10 (3rd February 2014) - Zhang, Lei; Zuo, Ziqing; Leng, Xuebing; Huang, Zheng
Abstract An extremely efficient cobalt catalyst for the hydroboration of both vinylarenes and aliphatic α‐olefins with pinacolborane is described, providing the anti‐Markovnikov products with excellent regio‐ and chemoselectivity, broad functional‐group tolerance, and high turnover numbers (up to 19 800). The alkene hydroboration route is further extended to a two‐step, one‐pot hydroboration and cross‐coupling of alkylboronates with aryl chlorides.